ANALISIS KORELASI KEPADATAN OPTIMUM IKAN DAN TANAMAN AIR PADA PEMELIHARAAN IKAN PATIN (Pangasius hypophthalmus) DENGAN SISTEM AKUAPONIK - muarofah ghofur; Ulil Azmi (Universitas Batangahari Jambi, 2020)
The purpose of this research is to know correlation the optimum fish and plant density of water for the maintenance of fish catfish (P. hypophthalmus) on akuaponik system in order to produce a high fish survival. As for the benefits of this activity is to improve the production results mainly from the fishery commodity fish catfish (P. hypophthalmus). This research plan will be implemented in February and July of 2019 in the porch Area Fish Seed Telanaipura the Province of Jambi. Research conducted using Randomized Block Design (RAK) wiyh four (4) treatment and three replicates, each treatment are : A treatment : 5 bar/hole, B treatment : 10 bar/hole, C treatment : 15 bar/hole, D treatment : 20 bar/hole. The research of the parameters observed were : survival rates of fish and water quality.